2000
DOI: 10.1590/s0100-879x2000001000005
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metanephrines: a novel and cost-effective test for pheochromocytoma

Abstract: Pheochromocytomas are rare chromaffin cell tumors that nevertheless must be excluded in large numbers of patients who develop sustained or episodic hypertension as well as in many others with suggestive symptoms or with a familial history of pheochromocytoma. Diagnosis of pheochromocytoma depends importantly on biochemical evidence of excess catecholamine production by a tumor. Imperfect sensitivity and specificity of commonly available biochemical tests and the low incidence of the tumor among the tested popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…Urinary free catecholamines and free metadrenalines were analysed simultaneously also by automated HPLC using the Gilson ASTEO™ system. The method and conditlons were as described by Green et al 21 Reference ranges for the catecholamines and for VMA and HVA were based on published data from 50 hypertensive patients being investigated for phaeochromocytoma but not subsequently found to have the disease. 25.27 Neither dietary nor drug restrictions were imposed.…”
Section: Methodsmentioning
confidence: 99%
“…Urinary free catecholamines and free metadrenalines were analysed simultaneously also by automated HPLC using the Gilson ASTEO™ system. The method and conditlons were as described by Green et al 21 Reference ranges for the catecholamines and for VMA and HVA were based on published data from 50 hypertensive patients being investigated for phaeochromocytoma but not subsequently found to have the disease. 25.27 Neither dietary nor drug restrictions were imposed.…”
Section: Methodsmentioning
confidence: 99%
“…These are constantly produced by the actions of catechol-O-methyltransferase on catecholamines leaking from stores within tumour cells and, therefore, show more consistent increases above normal in patients with phaeochromocytoma than plasma catecholamines, making this the more reliable test in these circumstances. [17][18][19][20] There is, however, still the possibility of false-positive results in which levels of metabolites are above the upper limit of normal, but not high enough to definitely diagnose phaeochromocytoma. Eisenhofer et al 6 have shown that, in such cases, clonidine suppression testing combined with measurement of plasma metanephrines can distinguish true-from false-positive results.…”
Section: Evaluation Of Clonidine Suppression Test CM Mchenry Et Almentioning
confidence: 99%
“…No variable on its own gives 100% precision (16). There is presently no consensus on the most reliable diagnostic method, providing the best quality/price ratio (17)(18)(19). Since 1998, assays of plasma fractionated metanephrines and of chromogranin A (CgA), a general indicator of neuroendocrine tumors that is highly expressed in pheochromocytomas, have been progressively widely developed and used (16,(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%